2020
DOI: 10.1186/s12985-020-01409-8
|View full text |Cite
|
Sign up to set email alerts
|

Chronic active Epstein–Barr virus infection manifesting as coronary artery aneurysm and uveitis

Abstract: Background Chronic active Epstein–Barr virus (CAEBV) infection is a type of lymphoproliferative disorder characterized by chronic or recurrent infectious mononucleosis (IM)-like symptoms, which can have less-frequent clinical presentations. The prognosis of CAEBV is poor, and hematopoietic stem cell transplantation (HSCT) has been shown to be the only potentially effective treatment. In this article, we present a special CAEBV case of a patient who had no typical IM-like symptoms at the early stage, but manife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 35 publications
0
24
0
3
Order By: Relevance
“…In 1988, Kobayashi et al first reported one child with CAEBV accompanied by dilation of left and right coronary arteries (14). Up to now, all cases of patients with CAEBV associated with CAL are reported from Japan (4,(6)(7)(8)15) and China (12,(16)(17)(18). Our patient in this case had multiple severe cardiovascular complications, her ECG showed second degree of AV block, and the echocardiogram revealed moderate mitral valve and tricuspid regurgitation, mild aortic regurgitation, bilateral SoV aneurysms, bilateral coronary artery lesions, aorta, and its branch dilations.…”
Section: Discussionmentioning
confidence: 99%
“…In 1988, Kobayashi et al first reported one child with CAEBV accompanied by dilation of left and right coronary arteries (14). Up to now, all cases of patients with CAEBV associated with CAL are reported from Japan (4,(6)(7)(8)15) and China (12,(16)(17)(18). Our patient in this case had multiple severe cardiovascular complications, her ECG showed second degree of AV block, and the echocardiogram revealed moderate mitral valve and tricuspid regurgitation, mild aortic regurgitation, bilateral SoV aneurysms, bilateral coronary artery lesions, aorta, and its branch dilations.…”
Section: Discussionmentioning
confidence: 99%
“…The elevated myocardial viral load, positive EBV protein in cardiomyocytes, and inflamed coronary intramural vessels confirmed the causal role of EBV [ 14 ]. Cardiovascular lesions in CAEBV could be strongly associated with EBV-infected T or NK lymphocyte infiltration and injuries in the vessel walls, and EBV-induced high levels of inflammatory cytokines [ 5 ]. Our case developed CAD when her clinical symptoms improved.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, other rheumatic diseases such as juvenile idiopathic arthritis (sJIA) and systemic lupus erythematosus (SLE) have also been reported to be complicated with coronary artery dilatation (34,35). In addition, there are some reports of coronary artery dilatation in patients with infectious diseases such as EBV virus infection and COVID-19 (36,37). It indicates that coronary artery dilatation may be more common than previously recognized.…”
Section: Discussionmentioning
confidence: 99%